Association between uric acid and cognitive function in maintenance hemodialysis patient - Avisek Maity; Ajay Kumar Sowthiri (Asian Journal of Medical Sciences, 2024)
Background: Chronic kidney disease (CKD) is an independent risk factor for cognitive dysfunction. Hyperuricemia is prevalent in CKD patients and has been associated with cognitive dysfunction. Hyperuricemia has been associated with an increased risk for cerebral microvascular disease. Aims and Objectives: The study aimed to evaluate the association between uric acid level and cognitive function in maintenance hemodialysis patients. Materials and Methods: The study was conducted on 90 maintenance hemodialysis patients. Serum uric acid (sUA) level was measured in patients on maintenance hemodialysis and cognitive performance was assessed by the Standardized Mini-Mental State Examination score. Results: There was a significant association between sUA level and cognitive function in hemodialysis patients. Patient with higher sUA levels was found to have poor cognitive function (P<0.05). There was a significant negative correlation between sUA and cognitive function which revealed an increase in sUA will decrease the cognitive function (P<0.05). In our study, there was a significant association between sUA and cognitive function in hemodialysis patients. Patients with hyperuricemia had poor cognitive function. Conclusion: In our study, there was a significant association between sUA and cognitive function in hemodialysis patients. Patients with hyperuricemia had poor cognitive function.